The Role of Physical Self-Efficacy in Enhancing Quality of Life Among Rural Filipino Youth - Marlon A. Mancera (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study examines the relationship between physical self-efficacy and the quality of life among rural Filipino youth. Methodology: The study employed a quantitative correlational design. Data were collected from 378 respondents selected via simple random sampling, using a validated physical self-efficacy scale and a quality-of-life assessment tool. Main Findings: Findings indicate that students exhibited moderate levels of physical self-efficacy and perceived quality of life. The analysis revealed a significant positive relationship between these variables, with a correlation coefficient of r = 0.439 r = 0.439 r = 0.439 (p-value = 0.001). This result suggests that higher physical self-efficacy is associated with improved life satisfaction, highlighting the importance of fostering confidence in physical abilities as a key contributor to overall wellbeing. Novelty/Originality of this study: This study underscores the pivotal role of physical self-efficacy in enhancing rural youth wellbeing, offering new insights into addressing disparities in resources and opportunities for physical activity. It contributes to sports and education policy by highlighting the need to prioritize physical education programs that build self-efficacy among rural youth. Additionally, the study provides practical applications for community-based interventions, such as designing inclusive sports initiatives and accessible recreational facilities, which can promote active lifestyles and holistic development. These findings serve as a foundation for crafting evidence-based strategies to support rural youth in overcoming socio-economic barriers and achieving improved physical, emotional, and social wellbeing.